2021
DOI: 10.1186/s12866-021-02086-5
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and antimicrobial potential of enterocin 12a from Enterococcus faecium

Abstract: Background Increase in the number of infections caused by Gram-negative bacteria in neutropenic cancer patients has prompted the search for novel therapeutic agents having dual anticancer and antimicrobial properties. Bacteriocins are cationic proteins of prokaryotic origin that have emerged as one of the most promising alternative antimicrobial agents with applications as food preservatives and therapeutic agents. Apart from their antimicrobial activities, bacteriocins are also being explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 63 publications
(71 reference statements)
0
20
0
Order By: Relevance
“…Studies show that patients suffering from neutropenic cancer are more susceptible to infections caused by Gram-negative bacteria. A recent study showed that enterocin 12 A produced by vaginal Enterococcus faecium can inhibit MDR Gram-negative bacteria such as Salmonella enterica , Shigella flexneri , Escherichia coli , and Vibrio cholerae , as well as the proliferation of cancer cells ( Sharma et al, 2021 ).…”
Section: Natural Products With Antibacterial Activitymentioning
confidence: 99%
“…Studies show that patients suffering from neutropenic cancer are more susceptible to infections caused by Gram-negative bacteria. A recent study showed that enterocin 12 A produced by vaginal Enterococcus faecium can inhibit MDR Gram-negative bacteria such as Salmonella enterica , Shigella flexneri , Escherichia coli , and Vibrio cholerae , as well as the proliferation of cancer cells ( Sharma et al, 2021 ).…”
Section: Natural Products With Antibacterial Activitymentioning
confidence: 99%
“…Bacteriocins are ribosomally synthesized antimicrobial peptides or proteins produced by several bacteria exhibiting narrow to wide range of antimicrobial spectrum against pathogenic bacteria such as different species of Listeria , Clostridium , Staphylococcus , Bacillus and others (Dai et al 2021 ; Fathizadeh et al 2021 ). The bacteriocins of probiotic bacteria have gained importance due to their safe applications in foods, pharmaceuticals, veterinary and human medicines (Barcenilla et al 2021 ; Liu et al 2011 ; Sharma et al 2021 ; Somashekaraiah et al 2021 ). These are inhibitory to narrow and broad range of bacteria by reducing cell viability and affecting the metabolism of bacterial cells or toxin production (Chen et al 2021 ; Sheoran and Tiwari 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppression which usually results due to anticancer drug regimen and destruction of the mucosal barrier due to utilizing invasive devices in cancer patients make them more vulnerable to different infectious diseases that need long-term prophylactic antibiotic regimens. 57 Moreover, the efficiency of antibiotic regimen to combat infections in cancer patients is compromised due to the growth of drug resistant bacterial pathogens that dominate in neutropenic patients. 58 Accordingly, novel anticancer agents that specifically suppress cancer cells having dual anticancer and antimicrobial activities are considered to act as prophylaxis against microbial infections alongside suppressing the growth of tumors in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“… 58 Accordingly, novel anticancer agents that specifically suppress cancer cells having dual anticancer and antimicrobial activities are considered to act as prophylaxis against microbial infections alongside suppressing the growth of tumors in cancer patients. 57,58 Accordingly, the new compounds were further subjected to antimicrobial investigation in comparison to amoxicillin trihydrate and clotrimazole as standard antibacterial and antifungal drugs, respectively, against a panel of Gram-positive, Gram-negative bacterial, yeast and fungal strains. In addition, minimum inhibitory concentrations were also assessed for the new candidates.…”
Section: Introductionmentioning
confidence: 99%